Associations between family care, organizational support, psychological resilience, and professional quality of life of emergency department nurses in China: A cross-sectional study - Gang Liu; Shaohua Hu; Peipei Ding (Belitung Nursing Journal, 2026)
Background: Emergency department nurses face substantial occupational stress due to frequent exposure to high-risk, unstable, and unpredictable clinical environments. However, research on nurses’ professional quality of life (ProQOL) has largely focused on other specialties, leaving ED nurses underrepresented. Addressing this gap is essential to improving professional well-being and job satisfaction. Objective: This study aimed to examine the associations between family care, organizational support, psychological resilience, and ProQOL among emergency department nurses. Methods: A cross-sectional study was conducted from July 6 to July 31, 2024, involving 441 emergency department nurses from 18 tertiary hospitals in 16 cities in Anhui Province, China. Data were collected using anonymous paper-based questionnaires and analyzed using descriptive statistics, t-tests, one-way ANOVA, Kruskal–Wallis H tests, Pearson’s correlation analysis, and multiple linear regression. Results: Compassion satisfaction differed significantly by sex (Z = -2.677, |d| = 0.231, p = 0.007), professional level (H = 17.675, η² = 0.035, p < 0.001), and number of night shifts (H = 10.571, η² = 0.022, p = 0.005). Burnout scores varied significantly by professional level (H = 8.861, η² = 0.016, p = 0.012), number of night shifts (H = 8.357, η² = 0.021, p = 0.015), and presence of chronic illness (Z = -2.029, |d| = 0.437, p = 0.042). Secondary traumatic stress differed significantly according to chronic illness history (Z = -2.232, |d| = 0.341, p = 0.026). Family care, organizational support, and psychological resilience were positively correlated with compassion satisfaction (r = 0.382, 0.549, and 0.562, respectively; all p < 0.001) and negatively correlated with burnout (r = -0.333, -0.405, and -0.497, respectively; all p < 0.001). Regression analyses indicated that family care, organizational support, and psychological resilience significantly predicted compassion satisfaction (adjusted R² = 0.458), while burnout was significantly associated with intention to leave the ED, family care, organizational support, and psychological resilience (adjusted R² = 0.358). Conclusion: The findings provide evidence that family care, organizational support, and psychological resilience are associated with the ProQOL of nurses working in emergency departments. In China, these results offer useful references for regions facing similar emergency care pressures (e.g., high workloads in tertiary hospitals, nurse shortages) to optimize nurse well-being interventions. They also provide a foundation for developing targeted strategies to enhance nurses’ professional well-being and job satisfaction.